The Politics of Population Growth - Ahmad, Dr. Salma (Journal of Political Studies, 2000)
With the exception of the spread of nuclear weaponry and threats to global ecological systems (although these are problems enough!), population growth is the most pressing and urgent issue currently faced by humanity (Giddens, 1994).